Adaptive Dynamic Programming For Chemotherapy Drug Delivery - Sun, Jiayue; Xu, Shun.; Liu, Yang.; Zhang, Huaguang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book focuses on the practical application of Adaptive Dynamic Programming (ADP) in chemotherapy drug delivery, taking into account clinical variables and real-time data. ADP's ability to adapt to changing conditions and make optimal decisions in complex and uncertain situations makes it a valuable tool in addressing pressing challenges in healthcare and other fields. As optimization technology evolves, we can expect to see even more sophisticated and powerful solutions emerge.
Preface -- Acknowledgements -- Chapter1 Introduction -- Chapter 2 Neural Networks-Based Immune Optimization Regulation Using Adaptive Dynamic Programming -- Chapter 3 Optimal Regulation Strategy for Nonzero-Sum Games of the Immune System Using Adaptive Dynamic Programming -- Chapter 4 Evolutionary Dynamics Optimal Research-Oriented Tumor Immunity Architecture -- Chapter 5 N-Level Hierarchy-Based Optimal Control to Develop Therapeutic Strategies for Ecological Evolutionary Dynamics Systems -- Chapter 6 Combination Therapy-Based Adaptive Control for Organism Using Medicine Dosage Regulation Mechanism.-Chapter 7 Adaptive Virotherapy Strategy for Organism with Constrained Input Using Medicine Dosage Regulation Mechanism -- References.
Keywords: Control engineering; Robotics; Automation; Drug delivery systems; Control, Robotics, Automation; Drug Delivery